Mode of action of the antimicrobial peptide Os on Candida albicans (ATCC 90028) biofilm formation - Gaspar, A.R.M. (Anabella Regina Marques) (University of Pretoria, 2024)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2019.